Education on Health Protocols and Improvement of the At-Taqwa Mosque Diro Bantul Landfill - Idiani Darmawati; Sigit Arie Wibowo; Yuningtyaswari; Iswanto Suwarno; Chapane Mutiua; Paul John Isaak; Amanollah Shojaei (Peneliti Teknologi Teknik Indonesia, 2023)
This community service stems from the problem of the Al Qur'an Education Park at the At-Taqwa Mosque Diro Bantul being inactive during the pandemic which was caused by unsafe conditions, low interest in learning by children, low parental awareness of the importance of religious education for children, and lack of active teachers. Seeing the importance of TPA as a means of developing children's spiritual intelligence and the importance of children's awareness of local wisdom, we took the initiative to reactivate activities at TPA which had been empty for a long time due to the Covid 19 pandemic. This service activity aims to increase children's interest in studying religion and culture in TPA also provides education on the 5M health protocol to TPA students, so that they can increase spiritual intelligence based on religion and local wisdom and increase awareness to comply with health protocols. By using participatory empowerment methods in partnership with the mosque takmir and youth of the At-Taqwa Diro Bantul mosque, this community service succeeded in carrying out a series of activities which included: Education on the 5 M health protocols, counseling for parents of students, training for TPA teachers, teaching at TPA with using learning modules and media through storytelling, group gymnastics and traditional games, equipping TPA facilities with the 5 M Health protocol facilities and infrastructure, and maintaining program sustainability by establishing the At-Taqwa Mosque Diro Bantul TPA management. The Service Team together with the management succeeded in increasing children's interest in learning to TPA and increased understanding of religion and local wisdom, as well as succeeded in increasing the discipline of the students in implementing the Covid 19 health protocol by implementing the Health protocol properly and correctly according to government guidelines.